Redefining Marketplace Payment On boarding: A Unified Global Payment Framework for Marketplace Scalability - Venu GopalaKrishna Chirukuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive examination of a transformative project that reimagined marketplace payment onboarding through the implementation of a unified global payment framework. The initiative addressed critical challenges faced by marketplace platforms operating across borders, including fragmented user experiences, technical debt accumulation, inconsistent security controls, operational inefficiencies, and limited scalability. Through a carefully architected solution built on React JS, Spring Boot microservices, and Kubernetes orchestration, the article implemented key innovations including universal payment provider integration, enhanced multi-factor authentication, and dynamic compliance management. The phased deployment strategy minimized disruption while validating system performance, resulting in dramatic improvements in seller onboarding time, support requirements, completion rates, and fraud prevention. The article examines technical challenges overcome during implementation, including integration complexity, data migration, and scalability under load, while detailing the multi-layered security approach that protected sensitive financial information through encryption, tokenization, behavioral analysis, and automated compliance controls. This work advances industry understanding of how unified payment frameworks can enable marketplace scalability in an increasingly global commercial landscape.